2017
DOI: 10.1007/s00432-017-2557-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LC3 and Beclin-1 autophagy genes suppresses proliferation, survival, migration and invasion by inhibition of Cyclin-D1 and uPAR/Integrin β1/ Src signaling in triple negative breast cancer cells

Abstract: Autophagy is a catabolic process for degrading dysfunctional proteins and organelles, and closely associated with cancer cell survival under therapeutic, metabolic stress, hypoxia, starvation and lack of growth factors, contributing to resistance to therapies. However, the role of autophagy in breast cancer cells is not well understood. In the present study, we investigated the role of autophagy in highly aggressive and metastatic triple negative breast cancer (TNBC) and non-metastatic breast cancer cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 56 publications
5
71
0
1
Order By: Relevance
“…Cell autophagy plays a momentous role in maintaining the stable structure and function of normal glomerular podocytes and proximal renal tubular epithelial cells [10]. Beclin-1 is a homologous gene of yeast autophagy gene Atg6/Vps30, which is one of the essential molecules of the formation of autophagosome [11]. LC3 is involved in the formation of autophagy, has been proved to be one of the common autophagosome marker proteins in mammalian cells [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell autophagy plays a momentous role in maintaining the stable structure and function of normal glomerular podocytes and proximal renal tubular epithelial cells [10]. Beclin-1 is a homologous gene of yeast autophagy gene Atg6/Vps30, which is one of the essential molecules of the formation of autophagosome [11]. LC3 is involved in the formation of autophagy, has been proved to be one of the common autophagosome marker proteins in mammalian cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…Beclin-1 is a homologous gene of yeast autophagy gene Atg6/Vps30, which is one of the essential molecules of the formation of autophagosome [11]. LC3 is involved in the formation of autophagy, has been proved to be one of the common autophagosome marker proteins in mammalian cells [11]. JNK and mTOR pathways have been testified to join in regulating cell apoptosis and autophagy in diverse diseases and also present the vital roles in the pathophysiology of DN [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…2 Beijing National Biochip Research Center Sub-Center in Ningxia, The General Hospital of Ningxia Medical University, Yinchuan 750004, China. 3 Medical Animal Lab, The Affiliated Hospital of Qingdao University, Qingdao 266003, China.…”
Section: Author Detailsmentioning
confidence: 99%
“…And the incidence and mortality of breast cancer have increased by nearly 18% since 2008 [2]. Breast cancer is a diverse hormone-dependent carcinoma, with both genetic and epigenetic changes leading to initiation, progression and metastasis [3]. Despite significant advances have been made in the biological development of breast cancer, the occurrence of metastasis still leads to poor prognosis and low survival.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in disease conditions of myocardial ischemia-reperfusion and neuronal ischemic anoxia, autophagy enhancement serves a role as a protective mechanism (37). Recent studies (38,39) have shown that drug-induced autophagy is characterized by the altered expression of autophagy-associated proteins LC3 and beclin1. LC3 and beclin1 are two pacemakers in the autophagic cascade.…”
Section: Discussionmentioning
confidence: 99%